2019
DOI: 10.1126/science.aay2346
|View full text |Cite
|
Sign up to set email alerts
|

Light-regulated collective contractility in a multicellular choanoflagellate

Abstract: Collective cell contractions that generate global tissue deformations are a signature feature of animal movement and morphogenesis. However, the origin of collective contractility in animals remains unclear. While surveying the Caribbean island of Curaçao for choanoflagellates, the closest living relatives of animals, we isolated a previously undescribed species (here named Choanoeca flexa sp. nov.) that forms multicellular cup-shaped colonies. The colonies rapidly invert their curvature in response to changin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(186 citation statements)
references
References 96 publications
7
179
0
Order By: Relevance
“…This is not generally regarded as a key factor in the origin of multicellularity in ancestors of Metazoa, but we suggest this should be considered. It is an interesting parallel that morphological and developmental changes (e.g., colony formation) in choanoflagellates can be also triggered by prey, although bacterial [94][95][96]. The functional basis for these changes requires further study, as does the relationship between the life cycle, morphology, formation of multicellular structures, and impacts of environmental change.…”
Section: Origins Of Multicellularitymentioning
confidence: 99%
“…This is not generally regarded as a key factor in the origin of multicellularity in ancestors of Metazoa, but we suggest this should be considered. It is an interesting parallel that morphological and developmental changes (e.g., colony formation) in choanoflagellates can be also triggered by prey, although bacterial [94][95][96]. The functional basis for these changes requires further study, as does the relationship between the life cycle, morphology, formation of multicellular structures, and impacts of environmental change.…”
Section: Origins Of Multicellularitymentioning
confidence: 99%
“…Moreover, S. rosetta is just one tip on the 285 choanoflagellate branch. A recent survey of 21 choanoflagellate transcriptomes revealed that choanoflagellates are at least as genetically diverse as animals (Richter et al, 2018), with other species retaining genetic pathways or exhibiting behaviors that are not found in S. rosetta (e.g., Marron et al, 2013;Leadbeater, 2015;Brunet et al, 2019). Together with future findings from S. rosetta, we anticipate that the establishment of genome editing in other choanoflagellates will 290 provide an increasingly complete portrait of the last common ancestor of choanoflagellates and animals.…”
Section: Discussionmentioning
confidence: 77%
“…This idea is based on the molecular phylogeny and morphological similarity between choanoflagellates and sponge choanocytes ( Fig.9 A-C) [38]. Further, the choanoflagellate colonies partially resemble the choanocyte chambers of the sponge [37,39,40]. In addition to their unicellular sister lineages, we also need to investigate other close relatives of the first multicellular animals.…”
Section: Lessons To Learn On the Origin Of Multicellularity Over The mentioning
confidence: 99%